Seroprevalence of Toxoplasma gondii and Neospora caninum in sheep intended for human consumption in the Rondônia state, Western Brazilian Amazon - Maia, Maerle Oliveira; Maia, Maiara Oliveira; Silva, Alexandre Redson Soares da; Gomes, Ana Amélia Domingues; Aguiar, Daniel Moura de; Pacheco, Richard de Campos; Costa, Alvimar José da [UNESP]; Santos-Doni, Thaís Rabelo dos (Elsevier, 2021)
The aim of this study was to carry out a seroepidemiological study of anti-T. gondii and anti-N. caninum antibodies in serum samples from sheep intended for human consumption in the Rondônia state, in the Western Brazilian Amazon, and identify possible risk factors associated with seropositivity. The analysis of the 616 sheep serum samples revealed animal-level seroprevalence of T. gondii in the order of 52.4 % and of N. caninum of 60.6 %. Prevalence of co-infections was 33.4 %. The herd-level seroprevalence was 100 % for both the parasites. Applying of multivariate logistic regression analysis, test of the association between seroprevalence of T. gondii infection and the potential predictors showed that feed, fetal malformation, abortion, neurological problems (lambs), presence of rodents were the significant (P < 0.05) predictors. The variables presence of rodents, cats, wild animals and main activity showed statistical association (P < 0.05) with the seroprevalence of N. caninum. Due to the high prevalence of T. gondii and N. caninum found in this study, the absence of specific slaughterhouses for sheep and raw or undercooked sheep meat for human consumption we concluded that sheep can represent an important source of infection for humans.
Keywords: Brazil; Neospora; Ovine; Prevalence; Toxoplasma; Western Amazon